Adherence to a Vegetable-Fruit-Soy Dietary Pattern or the Alternative Healthy Eating Index Is Associated with Lower Hip Fracture Risk among Singapore Chinese. Issue 4 (26th February 2014) - Dai, Zhaoli; Butler, Lesley M.; van Dam, Rob M.; Ang, Li-Wei; Yuan, Jian-Min; Koh, Woon-Puay
Abstract: Data on overall dietary pattern and osteoporotic fracture risk from population-based cohorts are limited, especially from Asian populations. This study examined the relation between overall diet and hip fracture risk by using principal components analysis (PCA) to identify dietary pattern specific to the study population and by using the Alternative Healthy Eating Index (AHEI) 2010 to assess dietary quality. The Singapore Chinese Health Study is a prospective population-based cohort that enrolled 63, 257 Chinese men and women (including both pre- and postmenopausal women) aged 45–74 y between 1993 and 1998 in Singapore. Habitual diet was assessed by using a validated food-frequency questionnaire. Two dietary patterns, the vegetable-fruit-soy (VFS) pattern and the meat-dim-sum (MDS) pattern, were derived by PCA. Overall dietary quality was assessed according to the AHEI 2010, which was defined a priori for chronic disease prevention. A Cox regression model was applied with adjustment for potential confounders. In both genders, higher scores for the VFS pattern and the AHEI 2010 were associated with lower risk of hip fracture in a dose-dependent manner (all P -trend ≤ 0.008). Compared with the lowest quintile, participants in the highest quintile had a 34% reduction in risk (HR: 0.66; 95% CI: 0.55, 0.78) for the VFS pattern and a 32% reduction in risk (HR: 0.68; 95% CI: 0.58, 0.79) for the AHEI 2010. The MDS pattern score was not associated with hip fracture risk. An Asian diet rich in plant-based foods, namely vegetables, fruit, and legumes such as soy, may reduce the risk of hip fracture.